Factors associated with retention in Quitline counseling for smoking cessation among HIV-positive smokers receiving care at HIV outpatient clinics in Vietnam. - Nam Truong Nguyen; Trang Nguyen; Giap Van Vu; Charles M Cleland; Yen Pham; Nga Truong; Reet Kapur; Gloria Guevara Alvarez; Phuong Thu Phan; Mari Armstrong-Hough; Donna Shelley (PLoS ONE)
Background Quitline counseling is an effective method for supporting smoking cessation, offering personalized and accessible assistance. Tobacco use is a significant public health issue among people living with HIV. In Vietnam, over 50% of men living with HIV use tobacco. However, there is limited research on Quitline use and retention rates in this population and a lack of research on factors associated with retention in Quitline counseling. The study aims to evaluate the factors associated with retention in Quitline counseling for smoking cessation among HIV-positive smokers receiving care at HIV outpatient clinics in Vietnam. Method The study analyzed data from a randomized controlled trial (RCT) that compared the effectiveness of three smoking cessation interventions for smokers living with HIV at 13 Outpatient Clinics in Ha Noi. A total of 221 smokers aged 18 and above living with HIV participated in Arm 1 of the RCT, which included screening for tobacco use (Ask), health worker-delivered brief counseling (Assist), and proactive referral to Vietnam's national Quitline (AAR), in which the Quitline reached out to the patient to engage them in up to 10 sessions of smoking cessation counseling. Retention in Quitline counseling was defined as participating in more than five counseling calls. The study used bivariate and logistic regression analyses to explore the associations between retention and other factors. Results Fifty-one percent of HIV-positive smokers completed more than five counseling sessions. Smokers living with HIV aged 35 or older (OR = 5.53, 95% CI 1.42-21.52), who had a very low/low tobacco dependence level (OR = 2.26, 95% CI 1.14-4.51), had a lower score of perceived importance of quitting cigarettes (OR = 0.87, 95% CI 0.76-0.99), had a household ban or partial ban on cigarettes smoking (OR = 2.58, 95% CI 1.39-4.80), and had chosen a quit date during the Quitline counseling (OR = 3.0, 95% CI 1.63-5.53) were more likely to retain in the Quitline counseling than those smokers living with HIV whose ages were less than 35, who had a high/very high tobacco dependence level, had a higher score of perception of the importance of quitting cigarettes, did not have a household ban on cigarettes smoking, and did not choose a quit date during counseling. Conclusion There is a high retention rate in Quitline counseling services among PLWHs receiving care at HIV outpatient clinics. Tailoring interventions to the associated factors such as age, tobacco dependence, perceived importance of quitting, household smoking bans, and setting a quit date during counseling may improve engagement and outcomes, aiding in the reduction of smoking prevalence among HIV-positive individuals.